2016
DOI: 10.1021/acsami.6b07177
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Strategy to Encapsulate Antibiotics in a Bioinspired CaCO3 Structure Enabling pH-Sensitive Drug Release Apt for Therapeutic and Imaging Applications

Abstract: Herein we demonstrate a bioinspired method involving macromolecular assembly of anionic polypeptide with cationic peptide-oligomer that allows for in situ encapsulation of antibiotics like tetracycline in CaCO3 microstructure. In a single step one-pot process, the encapsulation of the drug occurs under desirable environmentally benign conditions resulting in drug loaded CaCO3 microspheres. While this tetracycline-loaded sample exhibits pH dependent in vitro drug-release profile and excellent antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Besides this, the high loading capacity of CaCO 3 crystals provides an opportunity for slow long-term controlled release, which is of high interest for therapeutic applications. 65,66 A high content of the loaded protein would give an option to reduce the number of carriers for protein delivery (the crystals or other carriers assembled using the crystal, e.g. microcapsules).…”
Section: -33mentioning
confidence: 99%
“…Besides this, the high loading capacity of CaCO 3 crystals provides an opportunity for slow long-term controlled release, which is of high interest for therapeutic applications. 65,66 A high content of the loaded protein would give an option to reduce the number of carriers for protein delivery (the crystals or other carriers assembled using the crystal, e.g. microcapsules).…”
Section: -33mentioning
confidence: 99%
“…It possesses unique advantages due to their biocompatibility and the ability for loading different therapeutic agents. Studies show that CaCO 3 nano/microparticles can be used as vectors to deliver various biological substances such as drugs [143,148], proteins [111,143,147,149], peptides [150,151] and genes [132,152]. Due to high biocompatibility, biodegradability, and pH sensitive features, vaterite and ACC show promising potential for the development of the drug delivery system for cancer treatment [143,148].…”
Section: Calcium Carbonate Drug Carriersmentioning
confidence: 99%
“…The antibacterial activity and pH-dependent drug release have been observed for CaCO 3 microstructures containing tetracycline-entrapped polypeptides [150]. It has been shown that the encapsulated drug or the dye-conjugated peptide emits fluorescence suitable for optical imaging and detection, thereby making it a multitasking material.…”
Section: Calcium Carbonate Drug Carriersmentioning
confidence: 99%
“…Using this method, the antibacterial agents will not be released until bacteria are present. Many “smart release” methods have been applied in anti‐cancer treatment, taking advantage of the acidic environment inside tumor cells . Because bacteria favor a relatively acidic microenvironment, the pH‐sensitive smart release of antibacterial agents can be conducted locally; in contrast, if no bacteria are present, antibacterial agents will not be released in vivo.…”
Section: Active Antibacterial Ti Surfacementioning
confidence: 99%